Promotive Effect of Ginger Rhizome Extract Supplement on In Vitro Rooting of Persian Violet Shoot Tip Culture - Bodhipadma, Kitti; Noichinda, Sompoch; Kluiprasert, Perapon; Luekklin, Pattama; Raksri, Thitiporn; Leung, David W. M. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
Ginger is recognized for its economic value, which is derived from its rhizome that is often utilized as a spice and a herb. In plant tissue culture, various natural supplements are often added into culture media. Ginger rhizome extract has not been added to plant tissue culture media before, although it is anticipated to have plant hormones needed by plant tissue culture. This study was aimed to investigate if the indole-3-acetic acid (IAA) contents in the extracts from young and old ginger rhizomes might be related to their effects on Persian violet shoot tips cultured on media supplemented with the extracts. Spectrophotometric analysis revealed distinct IAA concentrations of 97.04 and 95.57 µg/mL in the extracts from young and old ginger rhizomes, respectively. Basal MS medium was then supplemented with these extracts at concentrations of 0, 5, 10, and 20 mL L-1 for culturing Persian violet shoot tips over 4 weeks. Remarkably, the medium supplemented with 5 mL L-1 of old ginger rhizome extract was the most effective in inducing root formation from Persian violet shoot tips under in vitro conditions, resulting in an average of 29 roots formed per shoot tip explant. In this treatment, the average root length was 6.7 cm, and maximum shoot height (3.6 cm) was also promoted. Therefore, the extract of old ginger rhizome distinctly stimulated both root and shoot development of Persian violet in vitro. This investigation supports the use of ginger rhizome extract (containing auxin) in plant tissue culture, particularly for enhancing propagation and development of Persian violet.